Alcohol consumption and hospitalization burden in an adult Italian population: prospective results from the Moli‐sani study. (14th December 2018) - Costanzo, Simona; Mukamal, Kenneth J.; Di Castelnuovo, Augusto; Bonaccio, Marialaura; Olivieri, Marco; Persichillo, Mariarosaria; De Curtis, Amalia; Cerletti, Chiara; Donati, Maria Benedetta; de Gaetano, Giovanni; Iacoviello, Licia; ,
Abstract: Background and aims: Epidemiological evidence on the impact of different alcohol drinking patterns on health‐care systems or hospitalizations is sparse. We investigated how the different average volumes of alcohol consumed relate to all‐cause and cause‐specific hospitalizations. Design: Prospective cohort study (baseline 2005–10) linked to a registry of hospital discharge records to identify hospitalizations at follow‐up (December 2013). Setting: Molise region, Italy. Participants: A total of 20 682 individuals (48% men, age ≥ 35 years) who participated in the Moli‐sani Study and were free from cardiovascular disease or cancer at baseline. Measurements: The alcohol volume consumed in the year before enrolment was classified as: life‐time abstainers, former drinkers, occasional drinkers and current drinkers who drank 1–12 (referent), 12.1–24, 24.1–48 and > 48 g/day of alcohol. Cause‐specific hospitalizations were assigned by Italian Diagnosis Related Groups classification or by ICD‐9 code of main admission diagnoses. Incidence rate ratios (IRR) of hospitalization were estimated by Poisson regression, taking into account the total number of admissions that occurred during the follow‐up per person. Findings: During a median follow‐up of 6.3 years, 12 996 multiple hospital admissions occurred. In multivariable analyses, life‐time abstainers and former drinkers had higher rates of all‐cause [IRR = 1.11, 95% confidence interval (CI) = 1.05–1.17 and IRR = 1.19, 95% CI = 1.02–1.31, respectively] and vascular (IRR = 1.14, 95% CI = 1.02–1.27 and IRR = 1.48, 95% CI = 1.24–1.76, respectively) hospitalizations compared with light alcohol consumers. Alcohol consumption > 48 g/day was associated with a higher rate of hospitalization for both alcohol‐related diseases (IRR = 1.74, 95% CI = 1.32–2.29) and cancer (IRR = 1.36, 95% CI = 1.12–1.65). The magnitude of the association between heavier alcohol intake and hospitalization tended to be greater in smokers than non‐smokers. No associations were observed with hospitalization for trauma or neurodegenerative diseases. Conclusions: Moderate alcohol consumption appears to have a modest but complex impact on global hospitalization burden. Heavier drinkers have a higher rate of hospitalization for all causes, including alcohol‐related diseases and cancer, a risk that appears to be further magnified by concurrent smoking.